The office is a beautiful place when everyone else works from home - Adams, Scott, 1957- (Adams, Scott, 1957- Dilbert book, 2021)
"At first, working from home during the global pandemic seems like a great opportunity for Dilbert to avoid the drudgery of office life... Soon, however, the boss hires a stalker to look through the windows of his employees' homes to make sure they're staying on task. And on top of their already low morale, Dilbert and colleagues begin suffering from social media poisoning and a curious addiction to hand sanitizer."--Front flap